Clinicopathologic Characterization of Children With B-Cell Non-Hodgkin Lymphoma Over 10 Years at a Tertiary Center in Cape Town, South Africa. Issue 4 (May 2020) - Kriel, Magdalena; Davidson, Alan; Pillay, Komala; Hendricks, Marc; Phillips, Lee-Ann
Abstract : Background: We characterized B-cell non-Hodgkin lymphoma (NHL) cases over 10 years at a tertiary children's hospital to contribute to the body of knowledge on pediatric lymphoma in developing countries with a high human immunodeficiency virus (HIV) burden. Methods: A retrospective cohort study was carried out using clinical and laboratory records of children newly diagnosed with B-cell NHL from January 2005 to December 2014. Results: Seventy-five children ⩽15 years of age were included. The majority had Burkitt lymphoma (n=61). Overall, (n=19) were HIV positive and 16% (n=12) had concurrent active tuberculosis. Bulky disease was present in 65.7% (n=46) and 30.1% (n=22) were classified as Lymphomes Malins B risk group C. The 5-year survival estimates for HIV-negative and HIV-positive children were similar in our cohort: 81% versus 79% for event-free survival and 85% versus 83.9% for overall survival. Of 3 children with Burkitt lymphoma, HIV, and Lymphomes Malins B group C, 2 died within 1 year. Conclusions: Irrespective of HIV status, the survival of children in our B-cell NHL cohort compares favorably with cure rates in developed nations, although advanced disease remains associated with a poor prognosis. Characterization of childhood NHL cases contributes to accurate risk stratification and tailored treatment. Abstract : Supplemental Digital Content is available in the text.